The development of guided-inquiry based student worksheets integrated with Islamic values on environmental pollution material - Dayana Fazira; Ummi Nur Afinni Dwi Jayanti (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Guided inquiry-based student worksheets (LKPD) that are integrated with Islamic values are still rarely developed. This research was conducted with the aim of developing LKPD, as well as testing validity, practicality and effectiveness in classroom learning. The method used is Research and Development (R&D) 4D model. Data was collected using validation sheets by media experts, materials, Islamic values material, biology teacher response questionnaires and class X MIA MAS Madinatussalam Deli Serdang students. The results of the study obtained a score of 96.15% in the